In situ ion beam sputter deposition and X‐ray photoelectron spectroscopy (XPS) of multiple thin layers under computer control for combinatorial materials synthesis. (26th May 2016) - Wilson, Thomas A.; Barlow, Anders J.; Foster, Michael L.; Bravo Sanchez, Mariela; Portoles, Jose F.; Sano, Naoko; Cumpson, Peter J.; Fletcher, Ian W.
Abstract : Deposition of ultra‐thin layers under computer control is a frequent requirement in studies of novel sensors, materials screening, heterogeneous catalysis, the probing of band offsets near semiconductor junctions and many other applications. Often large‐area samples are produced by magnetron sputtering from multiple targets or by atomic layer deposition (ALD). Samples can then be transferred to an analytical chamber for checking by X‐ray photoelectron spectroscopy (XPS) or other surface‐sensitive spectroscopies. The 'wafer‐scale' nature of these tools is often greater than is required in combinatorial studies, where a few square centimetres or even millimetres of sample is sufficient for each composition to be tested. The large size leads to increased capital cost, problems of registration as samples are transferred between deposition and analysis, and often makes the use of precious metals as sputter targets prohibitively expensive. Instead we have modified a commercial sample block designed to perform angle‐resolved XPS in a commercial XPS instrument. This now allows ion‐beam sputter deposition from up to six different targets under complete computer control. Ion beam deposition is an attractive technology for depositing ultra‐thin layers of great purity under ultra‐high vacuum conditions, but is generally a very expensive technology. Our new sample block allows ion beam sputtering using the ion gun normally used for sputter depth‐profiling of samples, greatly reducing the cost and allowing deposition to be done (and checked by XPS) in situ in a single instrument. Precious metals are deposited cheaply and efficiently by ion‐beam sputtering from thin metal foils. Samples can then be removed, studied and exposed to reactants or surface treatments before being returned to the XPS to examine and quantify the effects. Copyright © 2016 The Authors Surface and Interface Analysis Published by John Wiley & Sons Ltd.